Conservative treatment of acetabular both column fractures: Does the concept of secondary congruence work? - Gänsslen, Axel; Hildebrand, F; Krettek, C (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2012)
Complete separation of all bony fragments around the acetabulum in both column fractures can lead to extra-anatomical orientation of these fragments around the femoral head with the potential of a "secondary congruence". No long-term data are known in the literature. We could follow 35 patients were a both column fracture was treated non-operatively due to different reasons. Demographics, fracture type, additional fracture lesions (comminution, marginal impaction), the clinical and radiological result and joint failure (severe arthrosis, FHN, esc. THR) were analyzed. The mean age was 38 years, 27 patients were male, eight female. All but four were multiply injured with a mean ISS of 22 points. 16 patients had additional pelvic ring injuries the majority of patients showed a C1-fracture of the acetabulum (anterior column multifragmentary, posterior column simple). 31 patients healed in secondary congruence (88%). Primary displacement was half (11,4 mm, 3-27 mm) compared to patients without secondary congruence (20 mm, 17-22 mm). 80% of the patients had none or only slight pain and 77% had an excellent or good functional result (Merle d'Aubigne Score). The rate of joint failure due to non-union, femoral head necrosis, posttraumatic degenerative changes or pain was relatively low with 17% after a mean of 5 years following trauma. In selected patients, conservative treatment of both column fractures can lead to acceptable long-term results with a high rate of secondary congruence.
Keywords: Treatment Outcome; ortopedické výkony; Aged; senioři; lidé středního věku; Adolescent; Female; výsledek terapie; mužské pohlaví; fraktury kostí; acetabulum; lidé; Fractures, Bone; Acetabulum; Middle Aged; ženské pohlaví; Humans; Orthopedic Procedures; Male; mladiství